Hidden victims : the effects of the death penalty on families of the accused - Sharp, Susan F., 1951- (Critical issues in crime and society., 2005)
America is fascinated with murder, as evidenced by the media's elaborate and often sensational coverage of homicides, the plethora of recreated television crime programs-such as America's Most Wanted and Unsolved Mysteries-and the number of high-grossing films and best-selling novels that revolve around murder plots. We love to be afraid and we love to hate offenders. Murderers, particularly those sentenced to death, we consider to be unusually heinous, often sub-human, and entirely different from the rest of us. In Hidden Victims, sociologist Susan F. Sharp challenges this culturally ingrained perspective by reminding us that those individuals facing a death sentence, in addition to being murderers, are brothers or sisters, mothers or fathers, daughters or sons, relatives or friends. Through a series of vivid and in-depth interviews with families of the accused, she demonstrates how the exceptionally severe way in which we view those on death row trickles down to those with whom they are closely connected. Sharp shows how family members and friends-in effect, the indirect victims of the initial crime-experience a profoundly complicated and socially isolating grief process. Departing from a humanist perspective from which most accounts of victims are told, Sharp makes her case from a sociological standpoint that draws out the parallel experiences and coping mechanisms of these individuals. Chapters focus on responses to sentencing, the particular structure of grieving faced by this population, execution, aftermath, wrongful conviction, family formation after conviction, and the complex situation of individuals related to both the killer and the victim. Powerful, poignant, and intelligently written, Hidden Victims challenges all of us-regardless of which side of the death penalty you are on-to understand the economic, social, and psychological repercussions that shape the lives of the often forgotten families of death row inmates.